Avoiding the ‘Curse of Knowledge’ in Your Writing - Schriefer, Natalie (Inside Higher Ed)
When seeking an academic editor, you may want to consider a generalist, writes Natalie Schriefer, who suggests how to find the best one for your work. I became an academic editor by accident. In 2015, an acquaintance asked if I was up for some last-minute proofreading. He was an adjunct professor and the sole author on a short article. His revisions were due the next day, and he was nervous about his grammar, but he’d heard I had an English degree. Could he hire me? When I said yes, I thought I was agreeing to a one-off job. That it would turn into six years of us working together, and start my freelance editing career? The thought never crossed my mind.
Keywords: Career; Education; Events; Higher; Jobs; News; dept.hhs